Pengaruh Persepsi Dukungan Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Melalui Keterikatan Karyawan Sebagai Variabel Intervening Pada Karyawan PT X - Veronika, Mikha; Gustari, Irvandi; Sihite, Mombang (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research is based on the fact that companies that are growing rapidly often face challenges in maintaining optimal employee performance. Perceived organizational support is the extent to which employees feel supported by their organization and job satisfaction reflects the extent to which employees are satisfied with aspects of their work, this can affect employee performance. Important factors in influencing performance, with employee engagement indicating the level of emotional and cognitive commitment to their work and is believed to play an important role in linking perceptions of organizational support and job satisfaction with employee performance. This study aims to determine the effect of perceived organizational support and job satisfaction on employee performance with employee engagement at PT X as a mediating variable. The research method used is a quantitative approach where direct data collection is carried out using HR interviews and questionnaires to 120 PT X employee respondents. Data were collected using a survey that measures perceptions of organizational support, job satisfaction, employee engagement, and employee performance. This research is a quantitative study using the PLS (Partial Lead Square) statistical tool. Data analysis was carried out using multiple statistical regression techniques and path analysis to test the relationship between variables. The results showed that there was a positive and significant influence of perceived organizational support, job satisfaction, employee engagement, on employee performance. Perceived organizational support and job satisfaction have a significant effect on employee engagement, which in turn has a positive impact on employee performance. Employee engagement has been shown to play an important role in the relationship between perceived organizational support and job satisfaction and performance